MONITORING OF APPLICATION OF REFRACTORY MATERIALS AT THE ENTERPRISES OF THE REPUBLIC OF BELARUS - A. T. Volochko; A. A. Shipko; M. I. Demin; A. V. Budzinskaja (Литьë и металлургия)
It is shown that the production organization in the republic of fire-resistant materials of own production will allow to replace partially the imported materials and articles from abroad and to save considerable currency means.